Data Set on Content Excerpts from Relevant Literature for a Scoping Review of Evacuation Training Methods in Buildings - Leo Willem Menzemer (Lund University, 2022)
This Excel-file contains a set of data from a scoping review on methods for fire evacuation training in buildings. The review follows the PRISMA approach (Transparent Reporting of Systematic Reviews and Meta-Analyses) and systematically identifies 73 sources among scientific literature published between 1997 and 2022. The dataset contains information excerpted through a custom template on the employed training methods and technology, study information, participants, and contents of the discussion of the 73 sources of evidence that were identified in the systematic review process.
Keywords: evacuation, training, drill, fire, learning, serious game, augmented reality, virtual reality, VR; Civil Engineering; Samhällsbyggnadsteknik